Anemia dan Kekurangan Energi Kronis Selama Kehamilan Meningkatkan Kejadian Berat Badan Lahir Rendah (Studi Kasus Kontrol) - Yoga Tri Wijayanti (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2018)
Background: Low birth weight babies can have long-term effects, including developmental and growth disorders, stunting to degenerative diseases, such as diabetes. Purpose: This study was to determine the relationship of parity, anemia and KEK with LBW events in 2016. Methods: This study used a retrospective case control study design. Cases were low birth babies 2500 gr born preterm or term The minimum number of samples needed by researchers 18 samples of LBW cases with a control sample of 18 cases that did not experience LBW were selected using consecutive sampling techniques. Data analysis using univariate analysis and bivariate analysis using chi square. Results: Statistical test results showed that there was a relationship between SEZ and LBW events (p value 0.03 0.05; POR 8.0) and there was a relationship between risk parity and LBW events (p value 0.02 0.05; POR 6.75). Conclusion: Pregnant women with SEZ risk increase the incidence of LBW by 8.0 times. Meanwhile, pregnant women with risk parity have the risk of increasing the chance of 6.75 times giving birth to a baby with LBW. Pregnant women with high parity should carry out routine pregnancy visits to make early detection of possible pregnancy complications including KEK, so that early treatment can be carried out and LBW infants can be prevented